Methodology For Developing Healthy Eating Habits In Preschool Children - Ruziyeva Shahnoza Mirsaidovna (LPPM STIE KRAKATAU, 2025)
Purpose: This study aims to examine the methodology for developing healthy eating habits among preschool-aged children by integrating scientific and pedagogical approaches. The research seeks to identify effective educational strategies that enhance children’s understanding of nutrition, promote rational dietary behavior, and prevent micronutrient deficiencies during early childhood development. Research methodology: A descriptive and analytical research design was employed, combining literature review, observation, and pedagogical experimentation in preschool institutions for children aged 3–7. The study draws on global best practices and recommendations from the World Health Organization (WHO) and UNICEF, emphasizing interactive learning methods such as games, group discussions, and storytelling to promote positive eating behaviors. Results: Findings demonstrate that the use of play-based and participatory learning activities significantly improves children’s awareness of healthy food choices and fosters long-term behavioral changes. Collaboration between teachers, parents, and healthcare professionals enhances the effectiveness of nutritional education programs and supports the holistic development of preschoolers. Conclusions: Developing healthy eating habits in early childhood requires an interdisciplinary approach that combines pedagogy, health education, and family involvement. Implementing structured nutrition education programs within preschool settings can contribute to children’s physical growth, cognitive development, and overall well-being. Limitations: The study was limited to selected preschool institutions and did not include longitudinal assessment of behavioral outcomes. Contribution: This research provides practical insights into the integration of health education and pedagogy to form sustainable healthy lifestyle habits among young children.